Incorporação de enxertos ósseos e osseointegração em área de agenesia dentária maxilar. Caso clínico - Nascimento, Rodrigo Dias [UNESP]; Cardoso, Paula Elaine [UNESP]; Matuda, Fabio da Silva; Raldi, Fernando Vagner [UNESP]; de Moraes, Michelle Bianchi [UNESP] (Editora Cubo, 2017)
The high dental implant success rate is directly linked to the presence of adequate bone volume, which enables and maintains the osseointegration of dental implants. This study aimed to report a clinical case of a female with agenesis of the right maxillary lateral incisor (12), due to cleft lip and palate. Because the bone and mucosal defects of the area, the treatment planning comprised guided bone regeneration with the association of autogenous bone, platelet rich plasm (PRP), and expanded polytetrafluoroethylene membrane (e-PTFE, Gore-Tex), performed in 2005. After nine months, a new evaluation was carried out and revealed that the area was still not suitable for implant placement. Thus, an allogenous bone graft was planned. Elapsed another nine months, the implant was placed. After six months, the implant was reopened and a metal-ceramic crown was installed. The 5-year following-up appointment showed the presence of fistula with purulent secretion at the buccal cortical plate. We attempted to control the fistula with antibiotics and follow-up clinically and radiographically. The examinations suggested a communication with the right nasal cavity, which decreased until nowadays. The osseointegrated dental implant was in function, without symptomatology. The autogenous bone graft is still more effective than allogenous bone graft. Further studies are necessary to achieve better evaluations.
Bone grafting and osseointegration in the area of maxillary tooth agenesis. Case report
Keywords: Bone graft; Dental implant; Osseointegration